Francis Fukuyama, Identity: The Demand for Dignity and the Politics of Resentment, New York, Farrar, Straus and Giroux, 2018, 240 pp. - Leyva, Karel J. (Res Publica. Revista de Historia de las Ideas Políticas, 2020)
Reseña del libro de Francis Fukuyama, Identity: The Demand for Dignity and the Politics of Resentment, New York, Farrar, Straus and Giroux, 2018, 240 pp.